Induction of Antibiotic Formation of Strains of Rare Actinomycetes in Depth Cultivation - N. G. Kulikova; L. P. Terekhova (Антибиотики и Химиотерапия, 2020)
The research was carried out on the biosynthesis of antibiotics in cultures of rare actinomycetes, which are of interest as potential producers of new antibiotic substances. Due to the fact that the selected strains were inactive during deep cultivation on liquid nutrient media, the goal was to select the conditions for induction of antibiotic formation in these cultures of actinomycetes. The goal was achieved with the use of adrenaline and potassium salt of indole-3-acetic acid as activators of antibiotic formation.